Students' Understanding of Nature of Science in Islamic Private School - Safkolam, Roswanna; Nuangchalerm, Prasart; Zaky El Islami, R. Ahmad; Saleah, Phurkhonni (Jurnal Pendidikan Islam, 2023)
The objective of this study is to explore Muslim students’ level of understanding regarding the nature of science (NoS)and compare their understanding between genders in private Islamic schools in Thailand.Descriptive statistics and t-test independent was used to analyze the data.The results revealed that a majority of the participants held a transitional perspective on NoS. Furthermore, there were no statistically significant differences in NoS comprehension between genders at the .05 level. To enhance students' understanding of NoS in all domains, it is recommended that learning activities in private Islamic schools promote a reflective attitude towards NoS